Programa transformando juntos para mejorar la adaptación al cambio educativo en la IEI N° 159 Niño de Jesús de Praga Iquitos 2024 - Vargas Armas, Juana Juliana (2025)
This study rigorously evaluated the impact of the Transformando Juntos program on enhancing educational change adaptation at IEI No. 159 Niño de Jesús de Praga, Iquitos, during 2024. A longitudinal, pre-experimental, and field-based design with an evaluative approach was employed. The sample, consisting of 60 members of the educational community, including administrators, teachers, teaching assistants, support staff, and parents, was selected through purposive sampling to ensure representativeness. A case based assessment instrument, validated by subject-matter experts to ensure methodological rigor, was applied. Non-parametric statistical techniques were used due to the non-normal distribution of the data. The results demonstrated statistically significant improvements in the primary variable and its dimensions: participation in training, integration of educational technologies, administrative management, and effective communication. Measures of central tendency indicated a consistent increase in competencies related to change management, supporting the hypothesis of the program's effectiveness. These findings provide empirical evidence that Transformando Juntos constitutes a valid and relevant methodological strategy to strengthen institutional adaptation capacities within constantly evolving educational contexts. The program contributes to the development of managerial, technological, and communicative competencies that facilitate effective and sustainable change processes.